The Multi-Functional Roles of CCR7 in Human Immunology and as a Promising Therapeutic Target for Cancer Therapeutics - Alrumaihi, Faris (Frontiers in Molecular Biosciences, 2022)
An important hallmark of human immune system is to provide adaptive immunity against pathogens but tolerance towards self-antigens. The CC‑chemokine receptor 7 (CCR7) plays a significant contribution in guiding cells to and within lymphoid organs and is important for acquiring immunity and tolerance. The CCR7 hold great importance in establishing thymic architecture and function as well as naïve and regulatory T-cells homing in the lymph nodes. Similarly, the receptor is a key regulator in cancer cells migration as well movement of dendritic cells. This makes the CCR7 an important receptor as drug and prognostic marker. In this review, we discussed several biology roles of the CCR7 and its importance as a drug and prognostic marker.